Nasionale dienspligveterane se soeke na afsluiting (closure): "n Pastorale sorg uitdaging - Schoeman, Roelf (HTS teologiese studies, 2019)
National conscripts and their quest for closure:A Pastoral challenge. During the apartheid era, young white men were conscripted for military service in the South African Defence Force. After the demise of apartheid, these military veterans became part of the transformation process in the country. They were often not prepared for the emotional and psychological impact of the political, economic and social changes. Many of them found and still find it difficult to take their place among the citizenry of the country. The post-apartheid government provided no support for them to reintegrate into the community or to process the often long-lasting effects of war related trauma and moral injury. For many, this resulted in a lack of healing and closure on a psychological, moral and spiritual level. This article aims to contribute from a pastoral care perspective to the process of healing, closure and reintegration of this specific group. A holistic narrative approach integrates the contextual approach of Charles Gerkin, the philosophical counselling of Daniel Louw and the insights of Neil Anderson with regard to the connection between spirituality and identity. A contextual approach promotes a deeper understanding of the veterans and their needs in the context of their local communities, including faith communities. In these local communities, resources are available and should be utilised. Such a constructive engagement between veterans, local communities and faith communities can contribute to healthier individuals, families and communities as well as to a healthier society. Guidelines for pastoral support of these veterans that can contribute to their social and personal transformation and process of psychological closure are proposed.